2019
DOI: 10.3390/fermentation5020032
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bioconversion of Gelatinized Starchy Waste from the Rice Noodle Manufacturing Process to Lactic Acid and Maltose-Forming α-Amylase by Lactobacillus plantarum S21, Using a Low-Cost Medium

Abstract: A direct bioconversion of gelatinized starchy waste (GSW) to lactic acid by amylolytic lactic acid bacterium Lactobacillus plantarum S21 was investigated. Corn steep liquor (CSL) was selected as the most suitable low-cost nitrogen source for replacing yeast extract, beef extract, and peptone in De Man, Rogosa and Sharpe (MRS) medium. Plackett–Burman design results indicated that GSW and CSL were the two most nutrients that significantly influence lactic acid production, among eight medium components, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Therefore, the composition of this sample, in terms of trouble-free preparation, was chosen for further processing. Although Eudragit® E ( 20 , 21 ), like PEG ( 15 , 43 ), is commonly used to prepare fish medicated compound feed, starch is also beneficial as a substrate for which a longer survival of probiotics can be expected ( 44 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the composition of this sample, in terms of trouble-free preparation, was chosen for further processing. Although Eudragit® E ( 20 , 21 ), like PEG ( 15 , 43 ), is commonly used to prepare fish medicated compound feed, starch is also beneficial as a substrate for which a longer survival of probiotics can be expected ( 44 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…PBD offers an efficient route to optimize large number of variables and identifies the most significant variables. The design has been successfully applied in medium optimization by various previous studies [44][45][46][47]. CCD was employed to optimize the concentrations of these important three variables for maximum L-LA production.…”
Section: L-la Production From Mixed Glucose and Xylose By Coculture Fermentationmentioning
confidence: 99%
“…The PBD was used to find out the significant medium compositions for L-lactic acid production by the strain SCJ9 among eight medium components based on the modified MRS medium [34] Table 3. Analysis of the data by the linear regression to fit with the first-order model found that the model was highly significant at p-value < 0.0001 with R 2 and adjusted R 2 values of 0.9972 and 0.9909, respectively.…”
Section: Statistical Optimization Of Medium Composition For Lactic Acmentioning
confidence: 99%